Study of spicy raw materials vacuum microwave concoction and microwave drying - Потапов, Володимир Олексійович; Михайлова, Світлана Володимирівна; Ефремов, Юрій Іванович (Eastern-European Journal of Enterprise Technologies, 2014)
The paper deals with defining the influence of microwave energy source power and vacuumizing depth on spicy raw materials heating duration, studying the mass and moisture content kinetics in the microwave concoction and microwave drying under vacuumizing conditions. The purpose of the paper is to establish the kinetics of microwave concoction and microwave drying of the mixture of crushed roots of spicy vegetables under vacuumizing conditions and to obtain practical information on rational modes of their implementation. The object of research is microwave concoction and microwave drying processes under vacuumizing conditions. A mixture of crushed roots of spicy vegetables such as parsley, parsnip, celery, dill was used as the subject of research. The microwave mixture concoction was carried out within the moisture content 560...100 %, and microwave drying - 100...10%. It was determined that the final temperature of the product decreases from 93oC to 76oC with the increase in the vacuumizing depth in the working chamber within 80...40 kPa. The duration of its achievement with increasing the heating power from 0.5 kW to 2 kW reduces by 3.9...4.1 times, and with increasing the vacuumizing depth from 80 kPa to 40 kPa - by 21...25 %. In microwave concoction, the change in vacuumizing depth from 80 kPa to 40 kPa affects the moisture removal intensity mainly during periods of warming and constant speed and generally leads to the process duration increase by 13...20 %. In microwave drying, slight difference in the results of changes in weight and moisture content is observed only at the initial stage, but there is almost no difference in achievement duration of the final value of moisture content. Rational values of processes duration at different values of heating power and vacuumizing depth were defined. It is recommended to maintain a residual pressure 40...60 kPa to preserve physicochemical properties of raw materials.